Marketing Strategy Analysis to Increase Product Sales Volume: (Study at Blitar City RR Refill Drinking Water Depot) - Yudhistira, Raka Valentino; Nasyirudin, Muhammad (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2024)
The aim of this research is to analyze marketing strategies and internal and external environmental conditions in the RR refill drinking water depot. Based on research from a 4P marketing perspective (product, price, place and promotion) from the product side, the RR logo is distinctive and easily recognized by the public, and is an RO (Reserve Osmosis) drinking water product that has been laboratory tested and has received a certificate. appropriate from the competent authority. In terms of price, a 19 liter gallon costs Rp. 6,000 and the Bio Water type costs Rp. 8,000. This price is quite helpful for the local community, most of whose customers are traders and food stall entrepreneurs. In terms of location, the depot location is very easy to reach and is about 100 meters from the main road (provincial) of Blitar City. The promotional side involves personal sales, coming directly to the location by visiting consumers door to door, where employees will make presentations explaining the sales product to attract buyers.